Literature Review: Integration of Hybrid Renewable Energy Systems in Remote Areas - A, Sulaiman; Minarti, Minarti; Saputra, Rahmad Surya Hadi (Journal of Renewable Engineering, 2025)
The availability of equitable and sustainable energy in remote areas is a major challenge for national development, primarily due to limited infrastructure and electricity access from conventional grids. Hybrid energy systems that combine renewable energy sources such as solar, wind, and microhydro with energy storage or diesel backup have emerged as an adaptive solution to address energy needs in off-grid areas. This study uses a qualitative approach based on literature to explore relevant hybrid energy system integration practices, challenges, and models across various geographic and social contexts. The study identifies that the success of hybrid system implementation is determined not only by its technological configuration but also by local social, economic, and institutional factors. Technological advances such as the Internet of Things (IoT) and smart energy management systems have contributed to improving system efficiency and reliability. However, obstacles remain in the form of limited funding, low public energy literacy, and weak supporting policies at the regional level. Through a thematic synthesis of the literature from the past five years, this study formulates a local energy ecosystem-based integration model that encompasses modular technology, multilevel policies, and community empowerment. These results are expected to serve as a strategic reference in promoting a just and sustainable energy transition in underdeveloped regions.